Curcumin in colorectal cancer: mechanistic insights, pharmacological limitations, and translational perspectives - Li, Si-Qi; Zhu, Xiao-Ren; Qin, Bai-Chun; Chen, Min-Bin (Frontiers in Pharmacology, 2025)
Curcumin, a natural polyphenolic compound from Curcuma longa, has been extensively investigated for its potential role in colorectal cancer (CRC) prevention and therapy. Preclinical studies suggest that curcumin can modulate gut microbiota composition, influence immune cell subsets such as M1/M2 macrophages, Treg/Th17 cells, and CD8+ T cells, and interfere with oncogenic signaling cascades including NF-κB, PI3K/Akt, and Wnt/β-catenin. These findings collectively highlight curcumin as a biologically active compound with broad mechanistic relevance. However, most evidence derives from in vitro assays at supra-physiological concentrations or high-dose animal models, raising concerns about pharmacological validity and clinical translatability. Curcumin is also recognized as a pan-assay interfering compound (PAINS), which may account for part of its pleiotropic activity and complicates interpretation of preclinical findings. Clinical trials to date have largely confirmed safety and biomarker modulation but have not demonstrated clear improvements in progression-free or overall survival. In this review, we critically appraise the available preclinical and clinical evidence on curcumin in CRC, highlighting both its mechanistic promise and the substantial limitations that constrain its therapeutic relevance, while outlining priorities for future research.